1982
DOI: 10.1136/bmj.285.6356.1717
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal transit of six commonly used tablets and capsules.

Abstract: The oesophageal transit of six commonly used tablets and capsules containing barium sulphate was evaluated radiologically using fluoroscopy in 121 healthy volunteers. To determine the influence of the subject's position and the amount of water taken each subject swallowed three preparations while recumbent and standing and with 25 ml or 100 ml of water. Failure of swallowing (defined as oesophageal transit taking more than 90 seconds) occurred in 22% of 726 swallowings, but globus was complained of in only 33%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(92 citation statements)
references
References 10 publications
3
88
0
1
Order By: Relevance
“…When tablets and capsules are swallowed in the supine posture with small volumes of water they frequently lodge in the oesophagus (Channer & Virjee 1982Hey et al, 1982). There are two potential consequences of the delayed oesophageal transit of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…When tablets and capsules are swallowed in the supine posture with small volumes of water they frequently lodge in the oesophagus (Channer & Virjee 1982Hey et al, 1982). There are two potential consequences of the delayed oesophageal transit of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…19 The authors showed that this tablet, similar in size and shape to aspirin, can remain in the esophagus for up to 90 minutes after ingestion, if the individual remained supine during the whole period. When swallowing small round tablets, the transit of these tablets can be transiently held up at the upper esophageal sphincter, the aortic arch, and distal esophagus immediately proximal to the lower esophageal sphincter.…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…The esophageal transit of capsules seems not to be affected by the volume of water, but in the supine position, the smaller capsule may be slower to transit than the larger. 19 Twenty-six percent of patients in one survey of general practitioners said they had problems in swallowing tablets. 21 A prominent complaint was the size of the tablet, followed by the surface, form and taste of the tablet.…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…Compared to healthy subjects, patients with dysphagia reportedly experience more difficulty swallowing tablets and require an increased volume of water for tablet ingestion, a longer ingestion time, and an increase in the number of swallowing attempts [2][3][4]. In order to improve compliance with taking medication, investigations into the dosage forms and physical properties of tablets that can be easy to ingest have been conducted in the past [5,6]. The larger the tablets, the harder they are to ingest; conversely, if they are too small, they can be difficult to handle.…”
Section: Introductionmentioning
confidence: 99%